The Influence of Transformational Leadership and Workload on the Performance of BMKG Technicians during the Covid-19 Pandemic: Comparison Between Generations X, Y, and Z - Gregorius Setyadhi Budhi Dharmawan; Mafizatun Nurhayati; Hendri Satria WD (Universitas Mercu Buana, 2022)
The Covid-19 pandemic has an impact on all aspects of human life, including public organizations. An organization requires management related to efforts to achieve goals that depend on the performance of the individual organization in carrying out the assigned tasks. This study aims to examine the effect of transformational leadership and workload during the Covid-19 pandemic on the performance of the Meteorology, Climatology and Geophysics Agency (BMKG) technicians with an analysis focus on the comparison of generations X, Y, and Z. The population in this study were BMKG technicians who were scattered throughout in Indonesia by calculating the sample using the Slovin formula. The method used in this research is quantitative with instrument testing to determine the validity and reliability of the data, then classical assumption test, model accuracy test and hypothesis. The results of the study show that the data are normally distributed and valid, and transformational leadership has a positive effect with the largest value on Y generation, and workload has the largest positive effect on X generation.